RESEARCH ON UNBALANCED RESPONSE OF ULTRA-HIGH SPEED CENTRIFUGAL IMPELLER ROTOR SYSTEM - ZHANG Yong (Jixie qiangdu)
In order to avoid large vibration response and transcritical motion instability of ultra-high speed centrifugal impeller rotor system caused by unbalanced excitation, the unbalanced excitation response of ultra-high speed centrifugal impeller rotor system was analyzed by using Ansys rotor dynamics response analysis module and comprehensively considering the stiffness and damping of sliding bearing, the dynamic response of ultra-high speed centrifugal impeller rotor system under different unbalanced excitation was obtained.At the same time, DEWESoft vibration test system was used to track and record the rotating frequency vibration value of ultra-high speed centrifugal impeller rotor system, and compared with the unbalanced response analysis results, it was concluded that the dynamic balance accuracy level of the ultra-high speed centrifugal impeller rotor system should be better than G1 level. The unbalanced excitation response analysis and control method has been well verified by tests, which has important engineering application significance.